(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction. Child abuse and neglect is one of the most serious social and public health problems. In the most severe cases, child abuse and neglect results in the tragic death of a child. The general objectives are to determine the number of reports of abuse made by teachers, their knowledge of child abuse laws and reporting procedures, and their perceived deterrents in reporting abuse. Also to evaluate teachers' responses to case vignettes. Materials And Methods: The survey we developed for this study contained 12 questions. Questionnaire was based on teaching experience, teachers knowledge about child abuse and there attitude towards reporting child abuse.Results: Majority of the teachers have knowledge about child abuse, they are aware of the signs and symptoms of child abuse and child neglect but they are not reporting child abuse cases.Conclusion: Teachers are the next person they are in daily contact with after their guardians. This study clearly outlines the need for enhanced training in child abuse reporting laws and procedures for school teachers. There is a definite need for more thorough training for teachers on child abuse reporting. It can be concluded that teachers should have knowledge about child abuse.